2006
DOI: 10.1097/01.aog.0000227750.93984.06
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Office Hysteroscopy Compared With Traditional Hysteroscopy

Abstract: ClinicalTrials.gov, www.clinicaltrials.gov, NCT00319410

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 23 publications
3
45
0
3
Order By: Relevance
“…2,73 One trial randomized 126 women to vaginoscopy without anesthesia and the traditional approach with speculum, tenaculum, and 10 mL 3% mepivacaine intracervical block. 74 The hysteroscopy was performed with normal saline and a rigid 3.7-mm hysteroscope. The women in the vaginoscopy group had mean pain scores of 3.8 compared with 5.3 in the traditional group on a 0-to 10-point scale.…”
Section: Hysteroscopymentioning
confidence: 99%
“…2,73 One trial randomized 126 women to vaginoscopy without anesthesia and the traditional approach with speculum, tenaculum, and 10 mL 3% mepivacaine intracervical block. 74 The hysteroscopy was performed with normal saline and a rigid 3.7-mm hysteroscope. The women in the vaginoscopy group had mean pain scores of 3.8 compared with 5.3 in the traditional group on a 0-to 10-point scale.…”
Section: Hysteroscopymentioning
confidence: 99%
“…23 Of the 18 papers reporting data for pain relief, we excluded three from meta-analysis; two because data were reported as the median value 24 or the mean but without standard deviation or standard error, 25 precluding calculation of the standardised mean difference, and another because of differences in intervention between the groups in addition to the use of local anaesthetic. 26 Most of the papers used continuous visual analogue scales (VAS) to assess pain; other studies used ordinal numerical or descriptive scales. Most results were reported as mean or median pain scores.…”
Section: Study Selection Details and Qualitymentioning
confidence: 99%
“…In fact one study found that a vaginoscopic approach to hysteroscopy was significantly less painful than having the procedure done traditionally with a vaginal speculum and a local anaesthetic block. 26 Outpatient hysteroscopy is a multi-faceted procedure, and there are many factors that contribute towards pain. These can be categorised into factors related to the patient (such as menopausal status, reason for hysteroscopy) and procedural factors (such as the type of distension media, use of a speculum, use of a rigid or flexible hysteroscope).…”
Section: Researchmentioning
confidence: 99%
“…Following both procedures, patients usually consider the EMB to be more painful than hysteroscopy (author's personal experience). This is especially the case when hysteroscopy is performed by the Bettochi technique (11,12).…”
Section: Hysteroscopic Guided Embmentioning
confidence: 99%